Development of fl oating chitosan-xanthan beads for oral controlled release of glipizide - Kulkarni, Nilesh; Wakte, Pravin; Naik, Jitendra (International Journal of Pharmaceutical Investigation)
Introduction: The aim of the present work was to develop controlled release, fl oating and mucoadhesive beads of glipizide by using the polyionic complexation technique. Plasma half-life of glipizide being 2–4 h was selected for development of controlled release dosage form. Methods: Formulation batches were designed by employing chitosan as cationic and xanthan gum as anionic polymers. In vitro drug release was evaluated for the period of 24 h in phosphate buffer pH 7.4. Results: Sustained release of drug was observed in all formulation batches with % drug release ranging from 87.50% to 100.67%, no signifi cant effect on the drug release was observed after varying chitosan to xanthan gum ratio. Encapsulation effi ciency was found to be in the range of 79.48 ± 1.10–94.48 ± 1.52. In vitro bioadhesion studies showed that beads had satisfactory bioadhesive strength ranging from 67.11% ± 1.73% to 93.12% ± 1.56%. Buoyancy studies revealed that beads possess comparable fl oating capacity in the gastric fl uids. Swelling kinetics was carried in pH 1.2 and 7.4 buffers. Signifi cant difference (P < 0.05) in swelling kinetics was observed. Drug to polymer interaction was analyzed by Fourier transform infrared spectroscopy and differential scanning calorimetry studies. Scanning electron microscopy studies revealed that formed beads were discrete with rough and wrinkled surfaces. Conclusions: In conclusion, beads were successfully formed by employing chitosan and xanthan gum and showed to possess sustained release effect. Beads also showed pH dependent swelling kinetics, this property can also be applied for the drugs which are susceptible to the acidic environment in the stomach, and comparable bioadhesive and fl oating properties were also observed.
Keywords: Beads; chitosan; polyelectrolyte complexation; sustained release; xanthan gum